Pengaruh Model Pembelajaran Project Based Learning (PjBL) terhadap Hasil Belajar Siswa pada Materi Keanekaragaman Hayati di Kelas X MIPA SMA Negeri 6 Pulau Taliabu - Sulina Tamimu; Nurlia Nurlia; Abdul Muin Kenta (Universitas Muhammadiyah Luwuk, 2022)
Abstract: Project Based Learning (PjBL) is a student-centered learning model aimed at fostering a more disciplined and creative attitude, active learning so that it influences student learning outcomes. This study aims to determine the effect of the 1 Project Based Learning (PjBL) learning model on learning outcomes on biodiversity material in class X MIPA SMA Negeri 6 Taliabu Island. This research is a quasi-experimental research with a pretest and posttest control grup design. The research was conducted in the odd semester of 2022/2023. The population of the study was all student of class X MIPA SMA Negeri 6 Taliabu. The sampel consisted of 2 classes, class X MIPA 1 was gathered by 10 people as the control class, and class MIPA 2 was gathered by 19 people as the experimental class. The data analysis technique used the normality test, homogeneity test, and t-test using the SPSS application. The results showed that there was no significant effect of the Project Based Learning (PjBL) learning model on the learning outcomes of class X MIPA students at SMA Negeri 6 Taliabu Island with a t-count < t-table, namely 0.198 < 1.703 and a significant value of 0.844 > 0.05. This study can be concluded that it rejected, and stated there is on significant effect of used Project Based Learning (PjBL) learning model on student learning outcomes on biodiversity material in class X MIPA SMA Negeri 6 Taliabu Island. Keywords: Learning Outcomes, Preject Based Learning (PjBL)